Insecticide-impregnated ear tags for range cattle - G.L. Lynch; K.O. Zoellner; A.B. Broce; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1982)
When both cows and calves were double-tagged (one tag per ear) with ear tags impregnated with fenvalerate (Ectrin) or permethrin (Atroban), the calves gained faster (P<.01) than when neither cows nor calves were tagged. Double-tagged yearling heifers gained faster (P<.05) than did heifers without tags. When all cows had been double-tagged, tagging the calves did not increase calf weight gain.
Keywords: Cattlemen' s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Insecticide-impregnated ear tags; Heifers; Gain